Analisis Dampak Investasi Asing Langsung Terhadap Pertumbuhan Ekonomi dan Kesejahteraan Masyarakat di Negara Berkembang - Muhammad Fauzan; Abdi Rahman (Gema Cendekia Institute, 2025)
This study examines the relationship between Foreign Direct Investment (FDI) andeconomic growth and welfare in developing countries, combining a review of classicaltheory and the latest empirical evidence up to 2025. The study summarizes thetransmission mechanisms of FDI (technology transfer, capital increases, spillovereffects), assesses the conditions for recipient countries to optimally benefit from FDI,and evaluates the current macro context in which global FDI flows and those todeveloping countries experienced a sharp decline in the early 2020s. The results showthat FDI has the potential to increase growth and welfare but its effects are highlydependent on absorptive capacity (human capital, financial markets, institutions) anddomestic policies. Policy recommendations are aimed at strengthening domesticcapabilities, improving investment quality, and integrating sustainable developmentgoals.